Large-area, high-responsivity, fast and broadband graphene/n-Si photodetector. (25th January 2021) - Scagliotti, Mattia; Salvato, Matteo; De Crescenzi, Maurizio; Mishra, Neeraj; Fabbri, Filippo; Miseikis, Vaidotas; Coletti, Camilla; Catone, Daniele; Di Mario, Lorenzo; Boscardin, Maurizio; Castrucci, Paola
Abstract: A graphene/Si heterojunction device has been realized to overcome many different requests necessary to make it a versatile, widely used and competitive detector. The obtained photodetectors, which operate at room temperature, are sensitive in the spectral region from ultraviolet (240 nm) to infrared (2000 nm) and they can be used in different configurations that allow a high responsivity up to 10 7 A W −1, a rise time of a few nanoseconds, an external quantum efficiency greater than 300%, and a linear response for different light sources. This is allowed by the high quality of the graphene deposited on a large area of 8 mm 2, and by the interdigitated design of the contacts, both preserving the excellent properties of graphene when switching from nanoscale to macroscopic dimensions of commonly used devices.